Promoting transit oriented development typology in the transportation planning - Taki, Herika Muhamad; Maatouk, Mohamed Mahmoud H (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2018)
the community. However, there are a few problems along with these advancements, such as the ineffectiveness of modes and networks as well as the inefficiencies of time and cost. Therefore, this paper aims to promote the application of Transit-Oriented Development (TOD) based on typology from existing stations in the Jakarta Metropolitan Region (JMR), Indonesia. It is expected to be able to create a public transport system that is integrated with the needs of the community. It makes easy access to achieve their travel destinations. This paper uses spatial analysis to determine the various TOD typology by involving many variables and indicators. It also creates a spatial model and applies it to transport planning in the JMR. The results obtained are three typologies of TOD namely Regional, Urban and Suburban. All types of TOD scattered in JMR and it has a trend pattern. TOD Regional located in the central core of the JMR, Urban TOD in the center and suburban TOD outside the center. This study is very helpful in guide transportation planning where several stations and railways intersect with future projects such as LRT, MRT, and BRT. It is expected to improve an integrated and sustainable transport planning.